Macrobenthos of the sand biotops from the coast of south-weastern Crimea in 1992 - Sofia A Mazlumyan; N K Revkov; Yu Prosvirov; Elena A Kolesnikova (PANGAEA, 2020)
Macrofauna were sampled in 1992, collected from the Sevastopol area (Black Sea off the coast of south-weastern Crimea). The sampling took place with the devices: Grab (0.04 m^2) and Petersen Grab (0.1 m^2) at depths from 3 to 25 m. Three transects were located perpendicular to the coast at a distance of 100 m. Two samples were taken at each station (40 samples per area) The sampled material was washed with 1 mm mesh sieve system and preserved in 75% alcohol, which is known to preserve morphological structures without distortion. We avoided prior fixation in formalin in order to not damage calcareous taxa. For each species, the average abundance (Ind/m^2), the average wet biomass (g/m^2) and the number of species was recorded.